2012
DOI: 10.1111/j.1365-2869.2012.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between irritable bowel syndrome and restless legs syndrome in the general population

Abstract: Summary This study aimed to explore the association between restless legs syndrome and irritable bowel syndrome in an epidemiological cohort. We included 3365 adults, of whom 1602 were female (age 52.5 ± 7.5 years), who had participated in the Korean Genome and Epidemiology Study (2005–2006). The diagnosis of restless legs syndrome was based on the criteria proposed by the International Restless Legs Syndrome Study Group, and irritable bowel syndrome was defined according to the Rome II criteria. The prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 44 publications
(96 reference statements)
3
3
0
Order By: Relevance
“…In the previous study, only the relationship between RLS and depressive symptoms was analyzed; however, no correlation between depression severity and RLS was reported. 9 12 25 In the present study, we found that among the patients with depression (based on BDI scores) in the RLS group, 97% of them had severe depression. This result, for the first time, indicates that severe depression is overwhelmingly frequent in patients with RLS.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the previous study, only the relationship between RLS and depressive symptoms was analyzed; however, no correlation between depression severity and RLS was reported. 9 12 25 In the present study, we found that among the patients with depression (based on BDI scores) in the RLS group, 97% of them had severe depression. This result, for the first time, indicates that severe depression is overwhelmingly frequent in patients with RLS.…”
Section: Discussionsupporting
confidence: 53%
“… 20 In the previous study performed on the same Korea cohort population as this present study, depressive mood was correlated with RLS. 25 However, that study focused on the association between RLS and irritable bowel syndrome. For a more in-depth discussion, it will be important to analyze the characteristic severity of depression in the RLS group and evaluate the clinical features of patients with RLS comorbid with depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we found that SSRIs use was associated with an increased risk of RLS in male IBS patients. Our results are consistent with previous studies showing an association between antidepressant use and significantly higher risk of RLS in IBS patients [68, 23]. However, these studies are small-scale, cross-sectional, or case-control studies.…”
Section: Discussionsupporting
confidence: 93%
“…A couple of studies have suggested that sleep disorders, particularly restless legs syndrome (RLS), are possible comorbidities in IBS patients [6, 7]. According to the previous studies, nearly 25%–30% of IBS patients experience RLS [68].…”
Section: Introductionmentioning
confidence: 99%
“…The severity index was also higher in IBD cases than in controls. These findings concur with a previous Korean study by Yun and his colleagues,[ 35 ] who reported RLS to be 2.59 times more common in IBD than in the non-IBD group (9.7% vs 3.8%; P < 0.001), However, the reported prevalence in our study is much higher than the Korean population, which could be related to the differences in the studied population and the diagnostic assessment criteria used. Furthermore, Weinstock et al .…”
Section: Discussionsupporting
confidence: 90%